Sensor for visualized detection of mushroom toxins and preparation method and application thereof
By utilizing a mushroom toxin sensor based on molecular imprinting technology, which employs magnetic Fe3O4@SiO2 nanoparticles and Congo red dye particles, the sensitivity and specificity issues of mushroom toxin detection have been resolved. This enables rapid and visual detection without the need for complex instruments, making it suitable for field applications.
Patent Information
- Application Number
- CN202511377052.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-25
- Publication Date
- 2026-02-06
AI Technical Summary
Existing mushroom toxin detection methods have low sensitivity and poor specificity, making it difficult to achieve on-site real-time detection. Furthermore, they lack effective signal output methods and cannot achieve visual detection without complex instruments.
A sensor based on molecular imprinting technology is used, which uses magnetic Fe3O4@SiO2 nanoparticles as the core, imprints the recognition cavity of mushroom toxin template molecules on the surface, and loads Congo red dye particles. The release of the signal is controlled by acid hydrolysis, so as to realize signal amplification and visual detection.
It achieves highly sensitive and specific detection of mushroom toxins, enabling rapid and simple visual detection without the need for complex instruments, with detection limits as low as μg/L, making it suitable for rapid on-site screening.
Smart Images

Figure CN121476100A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biosensing and food safety detection technology, specifically to a sensor for the visual detection of mushroom toxins, its preparation method, and its application. Background Technology
[0002] In recent years, the number of mushroom poisoning outbreaks in China has been escalating, becoming one of the main causes of food poisoning in the country. Between 2012 and 2023, the Chinese Center for Disease Control and Prevention's "Emergency Public Health Incident Reporting and Management Information System" reported 653 mushroom poisoning incidents, resulting in 3,229 cases and 710 deaths. This accounts for about one-fifth of all reported food poisoning incidents and more than half of all food poisoning deaths, with a case fatality rate as high as 21.99%. From a public health and safety perspective, mushroom toxin detection is a crucial measure for preventing food poisoning incidents. Many poisonous mushrooms contain highly toxic components, such as α-amatoxins in Amanita mushrooms, where even small amounts can cause severe liver damage or even death. Establishing rapid and accurate toxin detection methods can effectively identify poisonous mushrooms, reduce the risk of accidental ingestion, and ensure public food safety.
[0003] Traditional methods for detecting mushroom toxins mainly include chemical colorimetric methods, chromatography, immunological detection, and chromatography-mass spectrometry (GC-MS). Among them, chemical colorimetric methods (such as the reaction of concentrated hydrochloric acid with amatoxins to produce a blue-green color) are simple and suitable for rapid on-site screening, but have low sensitivity and poor specificity, and are easily affected by sample matrix interference. Chromatographic methods (such as thin-layer chromatography and high-performance liquid chromatography) significantly improve sensitivity and separation ability, but sample pretreatment is complex and equipment costs are high, making it difficult to implement on-site detection. Although GC-MS is sensitive and accurate, it requires highly skilled operators, relies on large and complex instruments, and is time-consuming.
[0004] In recent years, molecularly imprinted technology (MIT) has provided a new approach to solving the above problems. Molecularly imprinted polymers (MIPs) are known as "artificial antibodies" and have advantages such as simple preparation, low cost, high stability, and tolerance to harsh environments. Existing studies have used MIPs for the enrichment and detection of mushroom toxins, for example, as solid-phase extraction packing material coupled with HPLC, or to construct fluorescence and electrochemical sensors. However, most existing MIP sensors still have the following limitations: (1) Most of them need to be coupled with large detection instruments, making it difficult to get rid of the dependence on equipment and realize true point-of-care testing (POCT); (2) The detection sensitivity still needs to be improved, especially in the case of not needing complex instruments; (3) There is a lack of effective signal output methods, making it difficult to realize semi-quantitative detection by visual visualization without instruments.
[0005] Therefore, there is an urgent need in this field for a new method that can combine the high selectivity of molecular imprinting technology with a simple and intuitive signal output method, in order to develop a novel sensor that is highly sensitive, highly specific, easy to operate, low in cost, and suitable for rapid on-site visual detection of mushroom toxins. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a rapid visual detection sensor for mushroom toxins based on molecular imprinting technology and dye displacement signal amplification, its preparation method and application.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a sensor for the visual detection of mushroom toxins, the sensor comprising magnetic molecularly imprinted polymers (MIPs) and dye particles loaded thereon. The magnetic molecularly imprinted polymers (MIPs) have magnetic Fe3O4@SiO2 nanoparticles as their core, with recognition cavities for mushroom toxin template molecules imprinted on their surface. The mushroom toxin template molecules are shown in formula (I). ; The dye particles are ZIF-8-NH2@CR@IPPA, a metal-organic framework material encapsulating Congo red (CR) dye and having a surface modified with an indole structure similar to that of mushroom toxins. The dye particles are pre-loaded onto the MIPs by binding to the recognition cavity of the MIPs through an indole structure on their surface that is similar to that of mushroom toxin template molecules.
[0008] Secondly, the present invention provides a method for preparing the sensor, comprising the following steps: (1) Preparation of Fe3O4@SiO2@C=C: Fe3O4@SiO2 was dispersed in anhydrous ethanol containing γ-methacryloxypropyltrimethoxysilane (MPS), and the mixture was ultrasonically dispersed and mechanically stirred to obtain vinylated Fe3O4@SiO2@C=C. (2) Preparation of MIPs: Fe3O4@SiO2@C=C obtained in step (1) was dispersed in DMSO, and toxin template molecules, methacrylic acid (MAA) and 4-vinylpyridine (4-VP) were added for pre-assembly. Then ethylene glycol dimethacrylate (EGDMA) and initiator 2,2'-azobisisobutyronitrile (AIBN) were added. The polymerization reaction was carried out under an inert atmosphere, followed by magnetic separation and elution to obtain MIPs. (3) Preparation of ZIF-8-NH2@CR: Congo red was dissolved in methanol and added to an aqueous solution of (CR)Zn(NO3)2·6H2O and triethylamine (TEA). The mixture was stirred and mixed. Then, an aqueous solution of 2-aminobenzimidazole (2-ABzIm) and 2-methylimidazole (2-MeIM) in methanol was added. After the reaction, ZIF-8-NH2@CR was collected by centrifugation. (4) Preparation of ZIF-8-NH2@CR@IPPA: 3-indolepropionic acid (IPPA) was activated by EDC / NHS and then reacted with ZIF-8-NH2@CR obtained in step (3) to obtain ZIF-8-NH2@CR@IPPA; (5) Preparation of MIPs@CR: The MIPs obtained in step (2) are incubated with the ZIF-8-NH2@CR@IPPA obtained in step (4) to load the dye particles into the imprint cavity, and finally the sensor material MIPs@CR is obtained.
[0009] Preferably, the Fe3O4@SiO2 particles in step 1 have a particle size of about 380 nm. They can be commercially available or prepared by referring to existing literature methods.
[0010] Preferably, in step (2), the molar ratio of MAA to 4-VP and EGDMA is 1-3:1-3:1-3; more preferably 2:1:2; the molar ratio of the toxin template molecule to 4-VP is 1:2.5; the mass molar ratio of Fe3O4@SiO2@C=C to 4-VP is 1:1 (unit: g / mmol); the heating polymerization reaction temperature is 50-80℃, preferably 70℃; and the reaction time is 8-14h, preferably 12h.
[0011] Preferably, the elution in step (2) uses a mixed solution of methanol and acetic acid as the eluent, wherein the volume ratio of methanol to acetic acid is 4 to 19:1, for example, it can be 8:2, 9:1, or 95:5, preferably 9:1.
[0012] Preferably, in step (3), the molar ratio of Zn(NO3)2·6H2O to Congo Red (CR) is 1 to 7:1, more preferably 3.5:1, and the reaction time is 1 to 2.5 h, more preferably 1.5 h.
[0013] Preferably, in step (5), the mass ratio of MIPs to ZIF-8-NH2@CR@IPPA is 1:0.5 to 1.25, more preferably 1:1; the reaction temperature is 37°C, and the reaction time is 1 to 4 hours, more preferably 2 hours.
[0014] Thirdly, the present invention provides the application of the sensor described above, or the sensor prepared by any of the above methods, in the detection of mushroom toxins.
[0015] Preferably, the mushroom toxin is any one of α-amatoxin, β-amatoxin, γ-amatoxin, ε-amatoxin, trihydroxyamatoxin, trihydroxyamatoxin amide, dihydroxyamatoxin amide, dihydroxyamatoxin carboxylic acid, carboxy(dihydroxy)amatoxin amide, phalloidin, and amatoxin.
[0016] Fourthly, the present invention provides a method for visually detecting mushroom toxins using the above-described sensor and the sensor prepared by the above-described method, comprising the following steps: a) Disperse the sensor in a solution containing a toxin template, adjust the pH to neutral, and incubate to allow toxin molecules to competitively bind to the imprinted cavity and displace dye particles into the solution; b) After magnetic separation, take the supernatant, add hydrochloric acid to decompose and release CR, and then add sodium hydroxide to make the solution colorimetric; c) Semi-quantitative detection can be performed by observing color changes with the naked eye, or quantitative detection can be performed by measuring the ultraviolet absorption intensity at 505 nm.
[0017] Preferably, the solvent in step (a) is anhydrous ethanol; the concentration of the sensor is 1 to 3 mg / mL, preferably 2 mg / mL; and the incubation time is 20 to 40 minutes, preferably 25 minutes.
[0018] Preferably, the concentration of the hydrochloric acid is 0.1 M, and the concentration of the sodium hydroxide is 0.1 M.
[0019] The beneficial effects of this invention are as follows: High sensitivity and signal amplification: The dye is encapsulated with a high loading capacity using the ZIF-8 frame and released in a controlled manner through acid hydrolysis, which achieves significant signal amplification and a detection limit as low as μg / L. High selectivity: Based on the specific cavities generated by molecular imprinting technology, it can effectively distinguish target toxins from structural analogs and has strong anti-interference ability; Quick and easy: The testing process requires no complicated instruments, the operation steps are simple, the whole testing process is short, and it is suitable for rapid on-site screening; Visual detection: Semi-quantitative judgment can be made by observing color changes with the naked eye, which is intuitive and easy to understand; Low cost: The preparation cost of MIPs is much lower than that of antibodies; High versatility: The sensor prepared using common fragments of multiple toxins as templates can detect a variety of mushroom toxins; Good practical applicability: It has good recovery rate in complex real-world samples and has great application potential. Attached Figure Description
[0020] Figure 1 This is a schematic diagram illustrating the construction principle of the sensor of the present invention; Figure 2 The hydrophilicity and hydrophobicity test results of the intermediate materials and sensors prepared in Example 1 were performed using a contact angle meter: 2A is ZIF-8-NH2, 2B is ZIF-8-NH2@CR, 2C is ZIF-8-NH2@CR@IPPA, 2D is Fe3O4@SiO2, 2E is MIPs, 2F is NIPs, 2G is Fe3O4@SiO2@C=C, 2H is MIPs@CR, and 2I is NIPs@C; Figure 3 Fourier transform infrared spectroscopy was used to analyze the intermediate materials prepared in Example 1 and the sensor detection results: Figure 3 A represents the infrared spectra of ZIF-8 (a), ZIF-8-NH2 (b), ZIF-8-NH2@CR (c), ZIF-8-NH2@CR@IPPA (d), CR (e), and IPPA (f); Figure 3 B represents the infrared spectra of Fe3O4 (a), Fe3O4@SiO2 (b), Fe3O4@SiO2@C=C (c), MIPs (d), NIPs (e), MIPs@CR (f), and NIPs@CR (g); Figure 4 A shows the X-ray diffraction patterns of ZIF-8, ZIF-8-NH2, ZIF-8-NH2@CR, and ZIF-8-NH2@CR@IPPA; Figure 4 B represents the Zeta potential diagrams for ZIF-8-NH2 (a), CR (b), ZIF-8-NH2@CR (c), IPPA (d), ZIF-8-NH2@CR@IPPA (e), Fe3O4 (f), Fe3O4@SiO2 (g), Fe3O4@SiO2@C=C (h), MIPs (i), NIPs (j), MIPs@CR (k), and NIPs@CR (l). Figure 5 Nitrogen adsorption-desorption isotherms for ZIF-8 (A), ZIF-8-NH2 (B), ZIF-8-NH2@CR (C) and ZIF-8-NH2@CR@IPPA (D); Figure 6 DLS images of Fe3O4@SiO2 (A), Fe3O4@SiO2@C=C (B), MIPs (C), NIPs (D), MIPs@CR (E) and NIPs@CR (F) are shown in the figure, with the corresponding SEM images in the inset. Figure 7A shows the absorbance of MIPs@CR detecting different concentrations of toxin molecules (0, 40, 80, 100, 150, 200, 250, 300, 400, 500, 600 μg / L); 7B shows the linear fitting of MIPs@CR; 7C shows the absorbance of NIPs@CR detecting different concentrations of toxin molecules (0, 40, 80, 100, 150, 200, 250, 300, 400, 500, 600 μg / L); 7D shows the visualization of MIPs@CR and NIPs@CR detecting different concentrations of toxin molecules (from left to right, corresponding to 0, 40, 80, 100, 150, 200, 250, 300, 400, 500, 600 μg / L). Figure 8 A represents the selectivity of MIPs and NIPs for different substances (toxin template, tryptophan, histidine, glutathione, and bovine serum albumin); 8B represents the competitiveness of MIPs and NIPs for different substances (toxin template, tryptophan, histidine, glutathione, and bovine serum albumin). Figure 9 Results for the anti-ion interference capability (A), reproducibility (B), and time stability (C) of MIPs@CR; Figure 10 A shows the linearity of MIPs@CR in detecting different concentrations of α-AMA (0, 50, 100, 150, 200, 250, 300, 400, 500, 600, 700, 800 μg / L), with the inset showing the visualization for each concentration; 10B shows the linear fit of MIPs@CR; 10C shows the linearity of NIPs@CR in detecting different concentrations of α-AMA (0, 50, 100, 150, 200, 250, 300, 400, 500, 600, 700, 800 μg / L); 10D shows the visualization of MIPs@CR in detecting different concentrations of β-AMA (top) and γ-AMA (bottom), with concentrations from left to right being 0, 50, 100, 150, 200, 250, 300, 400, 500, 600, 700, 800 μg / L. Figure 11 For the sensor preparation in Examples 1 and 11-18, the ΔAbs and IF for detecting toxin template molecules are: 11A represents different reaction temperatures (Examples 1 and 11-13), 11B represents different reaction times (Examples 1 and 14-16), and 11C represents different eluents (Examples 1 and 17-18). Figure 12 ΔAbs and IF for the detection of toxin template molecules by sensors prepared for Examples 1 and 19-24: 12A represents different dye loading amounts (Examples 1 and 19-21); 12B represents different dye loading times (Examples 1 and 22-24). Figure 13 The images show the UV spectra of the sensors synthesized in Examples 1 and 31. 13A shows the reaction times at different times during the synthesis of ZIF-8-NH2@CR (Examples 1 and 25-27), and 13B shows the amounts of different CRs added during the synthesis of ZIF-8-NH2@CR (Examples 1 and 28-31). Detailed Implementation
[0021] This invention first involves coating a layer of SiO2 onto the surface of magnetic Fe3O4, followed by modification with the silane reagent MPS, and then grafting C=C onto its surface. Finally, MAA and 4-VP are selected as functional monomers, and EGDMA is used as a crosslinking agent. In the presence of a toxin template, AIBN is added to initiate polymerization, embedding the toxin template into the crosslinked polymer network. MAA and 4-VP form hydrogen bonds, electrostatic interactions, and π-π interactions with the hydroxyl, carboxyl, and aromatic structures in the mushroom toxin molecule through carboxylic acid and pyridine groups, respectively, thereby synergistically enhancing the pre-assembled recognition ability of the toxin. EGDMA is chosen as the crosslinking agent because its bifunctional properties allow for the formation of a stable three-dimensional network structure during polymerization, maintaining the configuration of the imprinted cavity and improving the mechanical strength of the MIPs. AIBN is used as a thermal initiator, which can efficiently decompose under mild heating conditions to generate free radicals, driving the copolymerization reaction of the functional monomers and crosslinking agent, ensuring a controllable imprinting process and a homogeneous polymerization system.
[0022] This reaction system synergistically optimizes the selective adsorption and stability of MIPs for target toxins and reduces non-specific adsorption through the specific binding of functional monomers to template molecules, the structural support of cross-linking agents, and the reliable reactivity of initiators. After eluting the toxin template molecules, MIPs with specific recognition cavities for mushroom toxins are obtained. Additionally, by encapsulating Congo red within ZIF-8-NH2 and coupling it with IPPA, orange-red dye particles ZIF-8-NH2@CR@IPPA are obtained. Since the prepared dye particles have an indole structure similar to mushroom toxins, they can bind to the imprinted cavities on the MIPs, resulting in MIPs@CR. NIPs, on the other hand, non-specifically adsorb a small amount of dye onto their surface, resulting in NIPs@CR. When mushroom toxins coexist with MIPs@CR, the high specific binding ability of the toxins to the MIPs can displace the pre-loaded dye. Semi-quantitative detection of mushroom toxins can be achieved by observing color changes, and quantitative detection of mushroom toxins can be achieved by ultraviolet spectroscopy.
[0023] ZIF-8-NH2 is a porous metallic framework material that can efficiently encapsulate dye molecules and prevent leakage. However, it is susceptible to degradation in acid. Utilizing the protective encapsulation and acid-triggered controlled release characteristics of ZIF-8-NH2, when the dye ZIF-8-NH2@CR@IPPA is displaced into the solution, the addition of 0.1 M HCl causes H+ ions to bind to the imidazole ligands in ZIF-8-NH2, leading to framework dissociation and the release of a large amount of enriched dye. This concentrated release significantly increases the Congo red concentration in the detection system, generating a strong signal far exceeding that of a single dye molecule, thereby amplifying the detection sensitivity. The construction principle of the sensor in this invention is as follows: Figure 1 As shown.
[0024] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments, but this does not limit the present invention in any way. Any modifications or improvements made based on the teachings of the present invention shall fall within the protection scope of the present invention.
[0025] The processes, conditions, reagents, and experimental methods used in implementing this invention, except as specifically mentioned below, are all common knowledge and general knowledge in the field, and this invention does not have any particular limitations. Experimental methods in the embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer.
[0026] Unless otherwise stated, all technical terms and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. However, in the event of any conflict, the specification containing the definitions shall prevail.
[0027] Table 1 shows the main reagent sources in the following examples: Table 1 shows the main reagent sources and specifications in the examples.
[0028] The Fe3O4@SiO2 used in the following examples was prepared in the applicant's laboratory. The specific method is referenced in the literature (Dai Y, Jiang W, Zheng Y, et al. Recyclable molecularly imprinted polymers based on Fe3O4@SiO2 and PAMAM dendrimers for the determination of myosmine incigarettes[J]. Microchimica Acta, 2022, 189(12): 467.): 8.1 g FeCl3·6H2O was dispersed in 240 mL ethylene glycol and dissolved by sonication to obtain a clear orange solution. Then, 21.6 g NaAc and 6 g polyethylene glycol (6000) were added under stirring and dissolved by sonication. The solution was then transferred to a 50°C water bath and magnetically stirred at 700 r / min for half an hour to ensure thorough mixing. The solution was then transferred to a polytetrafluoroethylene reactor and reacted in a 200°C oven for 24 h. After the reaction was completed, the product was washed three times alternately with ultrapure water and anhydrous ethanol. The product was then dried in a vacuum oven at 60°C for 12 h to obtain 2.81 g of Fe3O4.
[0029] Subsequently, 0.5 g of the obtained Fe3O4 nanoparticles were weighed and dispersed in 50 mL of isopropanol containing 2 mL of ultrapure water. 5 mL of NH3·H2O was slowly added dropwise under mechanical stirring at 700 r / min. After stirring for 5 min, 2.5 mL of LTEOS was slowly added dropwise. After the addition was complete, the reaction was heated at 45 °C for 6 h. After the reaction was complete, the obtained product was washed several times with ultrapure water and anhydrous ethanol until the supernatant was clear and transparent. The product was then dried in a vacuum oven at 60 °C for 12 h to obtain 1.22 g of Fe3O4@SiO2.
[0030] Example 1 This embodiment provides a method for preparing a sensor for visual detection of mushroom toxins, which includes the following steps: (1) Preparation of Fe3O4@C=C 0.2 g of Fe3O4@SiO2 nanoparticles were dispersed in 150 mL of anhydrous ethanol containing 12 mL of MPS. The dispersion was ultrasonically carried out for 20 min, followed by mechanical stirring at 700 r / min at 37 ℃ for 24 h. After the reaction, the product was collected using a magnet and washed four times with anhydrous ethanol. The washed product was then dried in a vacuum oven at 60 ℃ for 12 h. Finally, 0.1830 g of Fe3O4@SiO2@C=C nanoparticles were obtained.
[0031] (2) Preparation of MIPs / NIPs 0.1 g of Fe3O4@SiO2@C=C was dispersed in 30 mL of DMSO. 0.04 mmol of toxin template, 0.2 mmol of MAA, and 0.1 mmol of 4-VP were added. The mixture was sonicated for 30 min and then pre-assembled at 37 °C for 2 h. Next, 0.2 mmol EGDMA was added to the solution and stirred for 30 min under an argon atmosphere. Then, 1 mL DMSO containing 6 mg AIBN was slowly added to the solution to initiate polymerization. The reaction was stirred at 70 °C for 12 h, collected by magnetic separation, and washed with water and methanol solution to remove unreacted functional monomers and toxin templates. Then, the product was washed with a mixed eluent of methanol and acetic acid (v / v=9:1), with 6 mL of eluent added each time. After ultrasonic dispersion, the product was placed on a water bath at 37 °C and shaken for 20 min. The washing was repeated six times to remove the toxin template. Finally, the product was washed with water and methanol until neutral and dried under vacuum at 60 °C for 12 h to obtain MIPs: 0.0907 g. In addition, following the above method, 0.0886 g of NIPs were prepared as a control without the addition of a toxin template.
[0032] (3) Preparation of ZIF-8-NH2@CR Take a 50 mL flask, weigh out 0.5 mmol of Zn(NO3)2·6H2O, add 0.7 mL of ultrapure water and 0.58 mmol of TEA. Weigh out 100 mg of CR and dissolve it in 3.3 mL of anhydrous methanol. After ultrasonic dispersion, add it dropwise to the above zinc salt solution and stir the mixture at 37 °C. At the same time, weigh out 1.67 mmol of 2-ABzlm and 5.64 mmol of 2-MeIM and disperse them in a mixture of 3.3 mL of ultrapure water and 1.7 mL of anhydrous methanol. After complete ultrasonic dissolution, add it dropwise to the above flask, and then add anhydrous methanol to make the total solvent volume 16.7 mL. Stir at 37 °C for 1.5 h. After the reaction was completed, the product was collected by centrifugation and washed several times with methanol until the supernatant was free of Congo red orange-red color. The obtained product was dried in a vacuum oven at 60 °C for 12 h to obtain ZIF-8-NH2@CR 0.8612 g.
[0033] (4) Preparation of ZIF-8-NH2@CR@IPPA 94 mg (0.5 mmol) of IPPA was dissolved in 4 mL of anhydrous ethanol, and 1 mL of EDC (0.5 mmol) was added. After stirring for 5 min, 1 mL of NHS (1 mmol) was added, and stirring was continued at 37 °C for 1 h to activate the carboxyl group. 200 mg of ZIF-8-NH2@CR was dissolved in 4 mL of anhydrous ethanol and ultrasonically dispersed for 20 min. Then, it was added dropwise to the activated IPPA. After the addition was complete, the mixture was shaken in a constant temperature water bath shaker at 37 °C for 12 h. After the reaction was complete, 30 mL of water was added to precipitate the product for 4 h. The product was collected by centrifugation and washed several times with water until the supernatant was colorless and transparent. The obtained product was dried in a vacuum oven at 60 °C for 12 h to obtain 0.2018 g of ZIF-8-NH2@CR@IPPA.
[0034] (5) Preparation of NIPs@CR: 20 mg of the obtained MIPs / NIPs powder and 20 mg of ZIF-8-NH2@CR@IPPA were dispersed in 10 mL of anhydrous ethanol. After sonication for 10 min, the mixture was incubated in a water bath at 37 °C for 2 h to allow the dye particles to enter the imprinted cavity of the MIPs. After the reaction was completed, the mixture was separated by a magnet and washed with ultrapure water and anhydrous ethanol until the supernatant was colorless and transparent. The resulting product was then dried in a vacuum oven at 60 °C for 12 h to obtain 0.0232 g of MIP@CR and 0.0191 g of NIPs@CR.
[0035] Material characterization To understand the properties of the materials used in the sensor fabrication process, a series of characterizations were performed on the aforementioned intermediate materials. Firstly, the hydrophilicity / hydrophobicity of nine related materials was tested using a contact angle meter, such as… Figure 1 As shown, the test results indicate that the surface wettability of the nine materials is closely related to their composition and modification: ZIF-8-NH2 ( Figure 2 A) has a water contact angle of approximately 115°, exhibiting hydrophobicity; ZIF-8-NH2@CR ( Figure 2 The water contact angle of B) is slightly smaller than that of ZIF-8-NH2. This is because CR is a hydrophilic substance, and during the synthesis of ZIF-8-NH2@CR, a small amount of CR may adhere to its surface, leading to increased hydrophilicity of ZIF-8-NH2@CR. However, the change is not significant, indicating that ZIF-8-NH2 did not cause structural changes after coating CR. Furthermore, after ZIF-8-NH2@CR reacts with IPPA, the water contact angle of ZIF-8-NH2@CR@IPPA (…) is significantly reduced. Figure 2 C) The hydrophobicity is significantly enhanced because IPPA has strong hydrophobicity. When the ZIF-8-NH2@CR surface is modified with an indole ring, the hydrophobicity is mainly manifested by the indole ring. Fe3O4@SiO2 ( Figure 2 The water contact angle of Fe3O4@SiO2@C=C is approximately 18°, exhibiting strong hydrophilicity. However, after modifying its surface with hydrophobic groups C=C, the water contact angle of Fe3O4@SiO2@C=C becomes significantly different. Figure 2 The contact angle of G) becomes 113°, and the hydrophobicity is significantly enhanced. MIPs ( Figure 2 E) and NIPs Figure 2 F) After imprinting, the polymer surface still exhibits hydrophobicity due to the lack of strongly polar groups; when both are pre-loaded with the hydrophobic dye ZIF-8-NH2@CR@IPPA, MIPs@CR ( Figure 2 H) and NIPs@CR ( Figure 2 The hydrophobicity of I) was slightly enhanced, indicating that the dye loading was successful.
[0036] Subsequently, Fourier transform infrared spectroscopy was used to characterize dye-related materials and imprinted polymer-related materials: such as Figure 3 As shown in Figure A, in the infrared spectrum of ZIF-8(a), 3134 cm⁻¹ -1 and 2923 cm -1 The two peaks are the stretching vibration peaks of CH, at 1579 cm⁻¹. -1 and 1460 cm -1 The peaks at 1145 cm⁻¹ are characteristic of the C=N and C=C rings of the imidazole ring. -1 Characteristic peaks of Zn-N can also be observed at this location. The infrared spectrum of ZIF-8-NH2(b) shows an additional peak at 3382 cm⁻¹ compared to ZIF-8. -1 and 3463cm -1 The NH stretching vibration peak at 2-ABzlm and 1621 cm⁻¹ -1 and 1268 cm -1 The presence of an NH bending vibration peak indicates that the amino group was successfully introduced into ZIF-8. The infrared spectrum of ZIF-8-NH2@CR (c) is basically consistent with that of ZIF-8-NH2, and compared with the characteristic peak of CR, it can be seen that CR has no effect on the spectrum of ZIF-8-NH2@CR, indicating that coating ZIF-8-NH2 with CR does not cause structural changes. In the spectrum of ZIF-8-NH2@CR@IPPA (d), IPPA appears at 1093 cm⁻¹. -1 Characteristic peak of CN, 1700cm -1 The stretching vibration peak at C=O and 3076 cm⁻¹ -1 The vibrational peak of aromatic hydrogen on the indole ring indicates that IPPA was successfully modified on the ZIF-8-NH2@CR surface.
[0037] Furthermore, the formation of Fe3O4, Fe3O4@SiO2, Fe3O4@SiO2@C=C, MIPs, NIPs, MIPs@CR, and NIPs@CR was also verified using infrared spectroscopy. Figure 3 As shown in B, the 802 cm⁻¹ spectrum of Fe₃O₄@SiO₂ (b) is shown. -1 and 1105 cm -1 The corresponding asymmetric stretching of O-Si-O and symmetric vibration of Si-O indicate successful SiO2 encapsulation. After imprinting polymerization, the infrared spectra of MIPs(d) and NIPs(e) are indistinguishable because the only difference in their synthesis conditions is the presence or absence of a toxin template in the polymerization. After template elution, the structural properties of MIPs and NIPs are identical. When MIPs and NIPs are pre-loaded with dye, the infrared spectra of MIPs@CR(f) and NIPs@CR(g) show an increase of 755 cm⁻¹. -1 Bending vibration at CH, 1309 cm -1 The stretching vibration of CN and 1506 cm -1 The C=C stretching vibration on the indole ring further indicates that the dye loading was successful.
[0038] Figure 4 Figure A shows the X-ray diffraction (XRD) patterns of ZIF-8, ZIF-8-NH2, ZIF-8-NH2@CR, and ZIF-8-NH2@CR@IPPA. The XRD pattern of ZIF-8 (a) is consistent with the theoretical characteristic diffraction peaks. The positions of the characteristic diffraction peaks of ZIF-8-NH2 after the introduction of amino group, ZIF-8-NH2@CR coated with Congo red, and ZIF-8-NH2@CR@IPPA modified with IPPA are basically unchanged, with only slight differences in intensity. This indicates that the crystal form of ZIF-8 has not changed significantly after coating with dye and modifying the indole ring, indicating that the dye synthesis was successful.
[0039] Figure 4B shows the Zeta potential diagrams for the above materials. ZIF-8-NH2(a) has a potential of +18.4 mV due to the presence of its amino group. CR(b) is an anionic dye with a negative potential; therefore, after coating ZIF-8-NH2 with CR, the CR neutralizes the positive charge on its surface, reducing the potential to approximately +7.2 mV. IPPA has a slightly negative potential; therefore, the potential of ZIF-8-NH2@CR@IPPA is further reduced to -16 mV due to the introduction of the indole ring. Furthermore, the change from Fe3O4@SiO2(g) to Fe3O4@SiO2@C=C(h) also indicates the successful modification of C=C. After imprinting polymerization, the potentials of MIPs(i) and NIPs(j) return to around -12mV due to the polymerization of functional monomers. Subsequently, the dye is preloaded, and the negative charge on the dye surface repels the negative charge on the surfaces of MIPs and NIPs, resulting in an overall decrease in surface charge density. This causes the Zeta potentials of MIPs@CR(k) and NIPs@CR(l) to tend to be neutral.
[0040] Figure 5 The nitrogen adsorption-desorption isotherms for dye particle-related materials are shown, with ZIF-8(A) having a specific surface area of 958.2428 m². 2 / g, consistent with the characteristics of large specific surface area in metal-organic framework materials. In contrast, the imidazole ligand of ZIF-8-NH2(B) after the introduction of an amino group is replaced by an amino group, and the amino group has strong steric hindrance, thus the framework shrinks and the specific surface area decreases to 926.2619 m² / g. 2 / g. After coating with CR, the CR is encapsulated in ZIF-8-NH2 through surface polymerization or in-situ growth, occupying part of the pores of ZIF-8-NH2. Therefore, the specific surface area of ZIF-8-NH2@CR(C) is reduced to 671.6021 m². 2 / g. The subsequently modified indole ring binds to the amino groups on the ZIF-8-NH2@CR surface. This modification, on the one hand, blocks the pores, occupying the remaining pores to form a dense monolayer structure; on the other hand, it increases the hydrophobicity of the material, leading to the partial closure of the ZIF-8-NH2@CR pores and a reduction in surface active sites, thus significantly decreasing the specific surface area to 58.2486 m². 2 / g. Overall, the changes in the specific surface area of the four materials follow a predictable pattern.
[0041] Furthermore, the particle size of the relevant materials was characterized using dynamic light scattering (DLS) and scanning electron microscopy (SEM). Figure 6As shown, the particle size of Fe3O4@SiO2 is approximately 380 nm. Subsequent modification with C=C groups on its surface resulted in a slight increase in particle size, approximately 410 nm, as observed by DLS results, and a rougher surface. Further imprinting polymerization led to the coating of the MIPs and NIPs with an imprinted layer, increasing the particle size to approximately 550 nm. After preloading with dye particles, a large number of indole rings on ZIF-8-NH2@CR@IPPA bound to the specific imprinted cavities and adhered to the MIPs surface, resulting in a significant increase in the particle size of MIPs@CR, approximately 870 nm. In contrast, NIPs lack specific cavities and can only non-specifically adsorb a small amount of ZIF-8-NH2@CR@IPPA through electrostatic adsorption or hydrogen bonding, thus their particle size is relatively smaller than that of MIPs@CR, approximately 730 nm.
[0042] Application Example 1: Visual Detection of Mushroom Toxin Templates 1 mg of MIPs@CR (or NIPs@CR) (prepared in Example 1) was dispersed in anhydrous ethanol, and a toxin template was added to fix the total volume at 500 μL. After shaking and incubating at 37°C for 1 h, the toxin template displaced the dye particles into the solution. Then, the magnetically imprinted polymer was separated using a magnet. 100 μL of 0.1 M hydrochloric acid was added to the separated supernatant to lyse the dye particles and release CR. After shaking for 10 seconds, the solution showed a pale blue-purple color. Then, 400 μL of 0.1 M sodium hydroxide was added to make Congo red appear orange-red under alkaline conditions. ΔAbs is the difference in the intensity of the UV absorption peak at 505 nm of the sensor supernatant before and after the addition of the toxin template. Semi-quantitative detection of the toxin was achieved by visually observing the color of the supernatant, and quantitative detection of the toxin was achieved by detecting the results of UV absorption spectroscopy.
[0043] 1. Linearity and detection limit Based on the above detection conditions, different concentrations of toxin templates were added for detection, and the changes in their ultraviolet absorption peak at 505 nm were recorded. The changes in the ultraviolet absorption intensity of the MIPs@CR and NIPs@CR detection systems with the concentration of toxin templates within the concentration range (0~600 μg / L) were investigated.
[0044] The results are as follows Figure 7 As shown, when the toxin template concentration is in the range of 80~500 μg / L, the UV absorption intensity of the MIPs@CR detection system exhibits a linear change. Figure 7 A), the linear regression equation was calculated based on the relationship between the change in absorbance ΔAbs of the supernatant and the concentration of the toxin template. The calculated linear regression equation is ΔAbs = 5.55 × 10⁻⁴ C - 0.041 ( Figure 7B). Based on the formula for calculating the limit of detection (LOD), LOD = 3δ / k (where δ is the standard deviation of the results obtained from 10 blank sample tests, and k is the slope of the linear regression equation), the LOD of the toxin template was calculated to be 2.47 μg / L. However, the NIPs@CR detection system, lacking an imprint cavity specifically recognizing the toxin template, did not show a significant regular change in its UV absorption intensity or solution color under different concentrations of toxin template. Figure 7 C and Figure 7 D).
[0045] 2. Selectivity and competitiveness L-tryptophan, L-histidine, glutathione, and bovine serum albumin were selected as similar target compounds to the toxin template. The same concentration of similar compounds as the toxin template was added to the detection system to study the selective recognition ability of MIP-CDs.
[0046] The results are as follows Figure 8 As shown in Figure A, L-tryptophan and L-histidine, due to the presence of groups similar to the mushroom toxin template (such as indole rings, amino groups, and carboxyl groups), may weakly interact with the imprinted cavity of MIPs, thereby displacing a small amount of dye. Glutathione, as a small peptide, may also non-specifically bind to the imprinted cavity in MIPs due to its thiol and carboxyl groups. Bovine serum albumin contains many groups similar to the template molecule, but its large size makes it almost impossible to enter the imprinted cavity in MIPs and displace the dye. Overall, the signal response values of these analogues are significantly lower than those of the toxin template, indicating that MIPs have excellent specific recognition ability for mushroom toxins.
[0047] Similarly, competitive experiments were conducted using analogues of the four toxin templates mentioned above, and the results were as follows: Figure 8 As shown in B, the properties and sizes of the various analogues are different, making it difficult for them to specifically bind to MIPs. They can only rely on non-specific displacement to release a small amount of dye. Therefore, when the toxin template and the competitor are added to the system at the same time, the absorbance of the supernatant increases slightly, but the change is not significant.
[0048] 3. Anti-interference, reproducibility, and time stability To investigate the ability of the prepared MIPs@CR sensor to detect real samples, Na, a common component of human serum, was selected. + K + Mg 2+ Ca 2+ HCO 3- HPO4 2-Glucose, L-proline, and L-alanine were used as interfering ions, and their concentrations were set to 50 μM, 25 μM, 25 μM, 25 μM, 25 μM, 10 μM, 25 μM, and 25 μM, respectively, to investigate their anti-interference performance.
[0049] The results are as follows Figure 9 As shown in Figure A, the detection results of MIPs@CR for toxin templates fluctuate slightly in the presence of interfering ions, but overall there is almost no interference. This indicates that the sensor has good anti-interference performance in the presence of complex ions and is expected to be able to detect toxins in complex matrices.
[0050] To investigate the differences between the prepared sensors, five batches of MIPs@CR were prepared according to the method in Example 1 for the detection of toxin templates. The results are as follows: Figure 9 As shown in B, the Abs values of the five different batches of MIPs@CR for detecting toxin templates remained essentially unchanged, indicating that the sensor has good reproducibility.
[0051] To investigate the time stability of the prepared sensor, the MIPs@CR prepared in Example 1 were placed for 0, 1, 2, 3, 4, and 5 weeks, and then used to detect the same concentration of target mushroom toxins. The results are as follows: Figure 9 As shown in Figure C, the Abs signal response value of the sensor decreases with the increase of placement time, but after one month, its signal response value is still more than 90% of the initial value, indicating that the sensor has little impact on stability after long-term placement.
[0052] 4. Simulate actual sample testing The practical application value of the prepared MIPs@CR was explored by using it to detect toxin templates in human serum samples diluted 100-fold and fresh mushroom extracts. Each test was performed in triplicate, and the results are shown in Tables 2 and 3. The results showed that the recoveries of the prepared MIPs@CR for toxin template detection in human serum were 98.24%–102.16%, and the recoveries in fresh mushroom extracts were 99.23%–103.98%. This indicates that the prepared MIPs@CR can provide a good detection method for the practical detection of toxin templates.
[0053] The preparation method of fresh mushroom extract is as follows: fresh mushrooms are dried and ground into powder. 0.5 g of the obtained mushroom powder is weighed and dispersed in 5 mL of extraction buffer (methanol:water:0.01M HCl=5:4:1, v / v / v). After sonication, the mixture is shaken at 37℃ for 1 h and the supernatant is collected by centrifugation.
[0054] Table 2 Results of toxin template detection in serum
[0055] Table 3 Results of toxin template detection in fresh mushroom extract.
[0056] 5. Universality test To verify that the constructed sensor can be applied to the universal detection of various mushroom toxins, three toxins with imprinted template structures in their molecular structures—α-amatoxin (α-AMA), β-amatoxin (β-AMA), and γ-amatoxin (γ-AMA)—were selected. The concentration gradients of these three toxins were visualized, and the results are as follows: Figure 10 As shown. The linearity and detection limit of α-AMA were investigated, as follows. Figure 10 As shown in Figure A, when using MIPs@CR to detect α-AMA, within the concentration range of 100-600 μg / L, the color of the supernatant gradually deepened with increasing α-AMA concentration, exhibiting a good linear relationship. Figure 10 As shown in B, the detection limit was calculated to be 6.92 μg / L according to the formula LOD=3σ / k, while the corresponding NIPs@CR showed no significant change. Figure 10 As shown in Figure C, β-AMA and γ-AMA were detected, and the visualization results are as follows. Figure 10 As shown in Figure D, the color of the supernatant gradually deepens with increasing concentrations of both toxins, and the visualization effect is good. This demonstrates that the designed sensor can be used for the visual detection of various mushroom toxins.
[0057] Example 2-10 The difference between Examples 2-10 and Example 1 is that the amounts of MAA, 4-VP, and EGDMA are different. The specific amounts are shown in Table 4 below. The rest are the same as in Example 1.
[0058] Table 4. Dosage of MAA, 4-VP, and EGDMA in Examples 2-10
[0059] Sensors were prepared using Examples 1-10 respectively for the detection of toxin template molecules (methods were the same as in Application Example 1). The UV absorbance of the supernatant before and after the addition of toxin was measured, and the imprinting factor IF (IF = ΔAbs) was calculated. MIPs@CR / ΔAbs NIPs@CR ΔAbs represents the difference in UV absorption of the supernatant before and after the addition of the toxin.
[0060] The results are shown in Table 5. MAA and 4-VP, as the main structural functional monomers of the imprinted layer, determine the number and strength of binding sites between MIPs and mushroom toxins. If the amount is too small, there will be insufficient recognition sites, and if the amount is too large, a thick imprinted layer may be formed, which will not only make it difficult to elute the toxin template, but also cause strong non-specific adsorption. EGDMA, as a crosslinking agent, mainly affects the mechanical strength and pore structure of MIPs. If the amount is too small, the imprinted polymer structure will be unstable. If the amount is too large, the crosslinking density will be too high, which will also increase the difficulty of eluting the toxin template. The optimal amounts of MAA, 4-VP and EGDMA are 0.2 mmol, 0.1 mmol and 0.2 mmol, respectively.
[0061] Table 5 Examples 1-10 Imprinting Factor IF
[0062] Examples 11-13 The difference from Example 1 is that the polymerization reaction temperature in step (2) is different. Examples 10-12 are 50℃, 60℃ and 80℃ respectively, and the rest is the same as Example 1.
[0063] Sensors were prepared using Examples 1 and 11-13 respectively for the detection of toxin template molecules (using the same method as in Application Example 1). The UV absorption of the supernatant before and after the addition of toxin was detected, and the imprinting factor IF (IF=ΔAbsMIPs@CR / ΔAbsNIPs@CR) was calculated, where ΔAbs represents the difference in UV absorption of the supernatant before and after the addition of toxin.
[0064] like Figure 11 As shown in Figure A, after adding toxin template molecules, the absorbance of sensor MIPs@CR prepared at 50-80℃ changed significantly. The IF value was optimal when the reaction temperature was 70℃, indicating that the temperature at this point can ensure sufficient binding strength while avoiding damage to the template molecule structure or excessive cross-linking of the polymer caused by high temperature.
[0065] Examples 14-16 The difference from Example 1 is that the polymerization reaction time in step (2) is different, with Examples 13-15 having 8h, 10h, and 14h respectively.
[0066] Sensors were prepared using Examples 1 and 14-16 respectively for the detection of toxin template molecules (methods were the same as in Application Example 1). The UV absorption of the supernatant before and after the addition of the toxin was detected, and the imprinting factor IF (IF = ΔAbs) was calculated. MIPs@CR / ΔAbs NIPs@CR ΔAbs represents the difference in UV absorption of the supernatant before and after the addition of the toxin.
[0067] like Figure 11As shown in B, after adding toxin template molecules to prepare the sensor, the absorbance of the sensor changed significantly when the reaction time was 8-12 hours. Too short a reaction time may lead to insufficient polymerization and failure to form a stable imprinted cavity, while too long a reaction time may lead to increased non-specific adsorption. The best effect was achieved with a reaction time of 12 hours.
[0068] Examples 17-18 The difference from Example 1 is that the volume ratio of methanol and acetic acid in step (2) is different. In Examples 16-17, the volume ratios of methanol and acetic acid are 8:2 and 95:5, respectively, and the rest are the same as in Example 1.
[0069] Sensors were prepared using Examples 1 and 17-18, respectively, for the detection of toxin template molecules (methods were the same as in Application Example 1). The UV absorption of the supernatant before and after the addition of the toxin was detected, and the imprinting factor IF (IF = ΔAbs) was calculated. MIPs@CR / ΔAbs NIPs@CR ΔAbs represents the difference in UV absorption of the supernatant before and after the addition of the toxin.
[0070] like Figure 11 As shown in Figure C, the absorbance of sensors prepared by adding toxin template molecules after the methanol and acetic acid volume ratios of 8:2, 9:1, and 95:5 all changed significantly. However, a suitable eluent can effectively remove the toxin template while retaining the imprinted cavity with specific binding sites, thereby improving the selectivity of MIPs. If the eluent is not chosen properly, it will not only lead to difficulty in template elution, but may even destroy the imprinted cavity structure and reduce the recognition ability of MIPs. The elution effect is best when the eluent is methanol:acetic acid (v / v) at a ratio of 9:1.
[0071] Examples 19-21, The difference from Example 1 is that the amount of ZIF-8-NH2@CR@IPPA added in step (5) is different. The amounts added in Examples 18-20 are 10 mg, 15 mg, and 25 mg, respectively. The rest is the same as in Example 1.
[0072] Sensors were prepared using Examples 1 and 19-21 respectively for the detection of toxin template molecules (using the same method as in Application Example 1). The UV absorption of the supernatant before and after the addition of toxin was detected, and the imprinting factor IF (IF=ΔAbsMIPs@CR / ΔAbsNIPs@CR) was calculated, where ΔAbs represents the difference in UV absorption of the supernatant before and after the addition of toxin.
[0073] The results are as follows Figure 12As shown in Figure A, when the dye concentration is too low, less dye is fixed in the specific cavities of MIPs, resulting in less dye being displaced during the identification of mushroom toxins. However, when the dye concentration is too high, it becomes more difficult to wash MIPs@CR, and dyes may aggregate, preventing mushroom toxins from displacing the dyes. On the other hand, NIPs also adsorb more dye, leading to increased non-specific adsorption and reduced selectivity. A dye concentration of 2 mg / mL yields the best results when loaded.
[0074] Examples 22-24 The difference from Example 1 is that the incubation time in step (5) is different, namely 1h, 3h and 4h, while the rest is the same as Example 1.
[0075] like Figure 12 As shown in Figure B, the absorbance of the sensors prepared by incubation for 1–4 hours after the addition of toxin template molecules changed significantly. When the incubation time was less than 2 hours, the dye could not fully enter the specific cavity of the MIPs, meaning that the amount of MIPs binding to the dye was low. When the incubation time was greater than 2 hours, the adsorption of dye by NIPs increased, and non-specific adsorption was enhanced. Therefore, 2 hours is the optimal incubation time.
[0076] Examples 25-27 The difference from Example 1 is that the reaction time in step (3) is different, namely 1 h, 2 h and 2.5 h, while the rest is the same as Example 1.
[0077] The ultraviolet absorption spectra of Examples 1 and 25-27 were measured, and the results are as follows: Figure 13 As shown in Figure A, the reaction time affects the coating effect of CR and the integrity of the ZIF-8 structure. Too short a reaction time may result in incomplete CR coating, preventing CR from fully penetrating the pores or surface of ZIF-8-NH2, leading to a low coating rate. Conversely, too long a reaction time may cause excessive growth or partial collapse of the ZIF-8-NH2 structure, resulting in pore blockage or dye molecule aggregation, thereby reducing the specific surface area and coating uniformity of the material. The best CR coating effect is observed at a reaction time of 1.5 h.
[0078] Examples 28-31 The difference from Example 1 is that the amount of CR added in step (3) is different, namely 50 mg, 200 mg, 300 mg and 400 mg.
[0079] The ultraviolet absorption spectra of Examples 1 and 28-31 were measured, and the results are as follows: Figure 13 As shown in B, the amount of CR added affects the CR coating effect and the integrity of the ZIF-8 structure, with the best effect achieved when the amount of CR added is 100 mg.
[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A sensor for visual detection of mushroom toxins, characterized in that, The sensor is composed of magnetic molecularly imprinted polymers (MIPs) and dye particles loaded thereon. The magnetic molecularly imprinted polymers (MIPs) have magnetic Fe3O4@SiO2 nanoparticles as their core, with recognition cavities for mushroom toxin template molecules imprinted on their surface. The mushroom toxin template molecules are shown in formula (I). ; The dye particles are ZIF-8-NH2@CR@IPPA, a metal-organic framework material encapsulating Congo red dye and having an indole structure similar to that of mushroom toxin on its surface. The dye particles are pre-loaded onto the MIPs by binding to the recognition cavity of the MIPs through an indole structure on their surface that is similar to that of mushroom toxin template molecules.
2. A method for preparing the sensor as described in claim 1, characterized in that, Includes the following steps: (1) Preparation of Fe3O4@SiO2@C=C: Fe3O4@SiO2 was dispersed in anhydrous ethanol containing γ-methacryloxypropyltrimethoxysilane, and after ultrasonic dispersion and mechanical stirring reaction, vinylated Fe3O4@SiO2@C=C was obtained; (2) Preparation of MIPs: Fe3O4@SiO2@C=C obtained in step (1) was dispersed in DMSO, and toxin template molecules, methacrylic acid and 4-vinylpyridine were added for pre-assembly. Then, ethylene glycol dimethacrylate and initiator 2,2'-azobisisobutyronitrile were added, and the polymerization reaction was carried out under an inert atmosphere. After magnetic separation and elution, MIPs were obtained. (3) Preparation of ZIF-8-NH2@CR: Congo red was dissolved in methanol and added to an aqueous solution of Zn(NO3)2·6H2O and triethylamine. The mixture was stirred and mixed. Then, an aqueous solution of 2-aminobenzimidazole and 2-methylimidazole in methanol was added. After the reaction, ZIF-8-NH2@CR was collected by centrifugation. (4) Preparation of ZIF-8-NH2@CR@IPPA: 3-indolepropionic acid was activated by EDC / NHS and then reacted with ZIF-8-NH2@CR obtained in step (3) to obtain ZIF-8-NH2@CR@IPPA; (5) Preparation of MIPs@CR: The MIPs obtained in step (2) are incubated with the ZIF-8-NH2@CR@IPPA obtained in step (4) to load the dye particles into the imprint cavity, and finally the sensor material MIPs@CR is obtained.
3. The method according to claim 2, characterized in that, In step (2), the molar ratio of methacrylic acid to 4-vinylpyridine and ethylene glycol dimethacrylate is 1-3:1-3:1-3; the molar ratio of the toxin template molecule to 4-vinylpyridine is 1:2.5; the mass molar ratio of Fe3O4@SiO2@C=C to 4-vinylpyridine is 1:1 (unit: g / mmol); the heating polymerization reaction temperature is 50-80℃; and the reaction time is 8-14h.
4. The method according to claim 2, characterized in that, The elution in step (2) uses a mixed solution of methanol and acetic acid as the eluent, wherein the volume ratio of methanol to acetic acid is 4 to 19:
1.
5. The method according to claim 2, characterized in that, In step (3), the molar ratio of Zn(NO3)2·6H2O to Congo Red is 1-7:1, and the reaction time is 1-2.5h.
6. The method according to claim 2, characterized in that, In step (5), the mass ratio of MIPs to ZIF-8-NH2@CR@IPPA is 1:0.5 to 1.25, the reaction temperature is 37°C, and the reaction time is 1 to 4 hours.
7. The application of the sensor according to claim 1 or the sensor prepared by the method according to any one of claims 2-6 in the detection of mushroom toxins.
8. The application according to claim 7, characterized in that, The mushroom toxin is any one of α-amatoxin, β-amatoxin, γ-amatoxin, ε-amatoxin, trihydroxyamatoxin, trihydroxyamatoxin amide, dihydroxyamatoxin amide, dihydroxyamatoxin carboxylic acid, carboxy(dihydroxy)amatoxin amide, phalloidin, and amatoxin.
9. A method for visually detecting mushroom toxins using the sensor as described in claim 1 or a sensor prepared by the method of any one of claims 2-6, characterized in that, Includes the following steps: a) Disperse the sensor in a solution containing a toxin template, adjust the pH to neutral, and incubate to allow toxin molecules to competitively bind to the imprinted cavity and displace dye particles into the solution; b) After magnetic separation, take the supernatant, add hydrochloric acid to decompose and release CR, and then add sodium hydroxide to make the solution colorimetric; c) Semi-quantitative detection can be performed by observing color changes with the naked eye, or quantitative detection can be performed by measuring the ultraviolet absorption intensity at 505 nm.
10. The method according to claim 9, characterized in that, The solvent in step (a) is anhydrous ethanol; the concentration of the sensor used is 1–3 mg / mL; and the incubation time is 20–40 minutes.